Inovasi Pelayanan Publik Bupati Ngantor Di Desa (BUNG DESA) Kabupaten Labuhanbatu Utara - Setiadi; Sigiro, Benny (Sawala : Jurnal Administrasi Negara, 2024)
Difficult road access and long travel distances in several areas of Labuhanbatu Utara Regency have become the main obstacles for the community in obtaining public services. In response to this issue, the Head of the Labuhanbatu Utara District launched an integrated service innovation through the "Bupati Ngantor di Desa" program. (Bung Desa). This program focuses on providing public services in one location for one day to improve community accessibility to government services. This article aims to analyze the effectiveness of the Bung Desa program as an innovation in improving the quality of public services in Labuhan Batu Utara Regency. This research uses a literature study method that includes searching for scientific references through Google Scholar and news sources related to the Bung Desa program. Relevant articles are classified based on publication year, keywords, and journal content, while news is categorized according to source, relevance, and publication time. The research results show that the Bung Desa program adopts the principles of New Public Management (NPM) and has had a positive impact. This innovation not only improves service accessibility even to remote villages but also encourages community participation in development. The success of this program is influenced by several factors, such as the awareness and capability of the apparatus, implementation regulations, and the availability of facilities and infrastructure. However, improving road infrastructure remains a priority to support smooth accessibility. In addition, the publication of schedules and activities of the Bung Desa program through official media, such as the local government website, needs to be improved to expand the reach of information to the public